PERAN STRATEGIS ORGANISASI KEMASYARAKATAN ISLAM DALAM PEMBANGUNAN PERADABAN DAN KEBUDAYAAN MUSLIM DI INDONESIA - Saputra, Rezwandi; Hilzandri, Muhammad; Nurzena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The proliferation of Islamic-based civil society organizations in Indonesia constitutes one of the decisive factors in shaping Muslim civilizational identity across the archipelago. This study focuses on a systematic analysis of the contributions of five Islamic organizations with significant historical records and influence—Al-Irsyad AlIslamiyah, Al-Ittihadiyah, Al-Khairat, Muhammadiyah, and Nahdlatul Ulama (NU)—in constructing a distinctively characterized Islamic civilization in Indonesia. The research adopts a qualitative paradigm employing a historical-comparative approach grounded in an extensive literature review. Findings indicate that all five organizations have carved out monumental contributions, particularly in the transformation of educational systems, social order development, Islamic missionary activities (da'wah), and the internalization of Islamic principles harmonized with local wisdom. Muhammadiyah and NU occupy the most strategic positions given their far-reaching influence, while Al-Irsyad Al-Islamiyah, AlIttihadiyah, and Al-Khairat play equally vital roles within their respective regional contexts. This study's findings affirm that the presence of Islamic mass organizations has forged a typology of Islam characterized by moderatism, cultural pluralism, and compatibility with Indonesia's diverse local identities.